Ants associated with sucking insects in the aerial part of the coffee tree - FRANCO-R., ALEXANDRA; CÁRDENAS-M., REINALDO; MONTOYA, ESTHER CECILIA; DE POLANÍA, INGEBORG ZENNER (Revista Colombiana de Entomología, 2003)
Ants are found isolated or associated with other insects, directly or indirectly affecting the coffee plants. In order to clarify some of these associations, in coffee plantations, younger than three years, ants and associated homopteran insects were collected and identified, the relationships described and a field guide for identification of the formicids elaborated. The study was carried out in seven experimental substations of Cenicafé. The data obtained from the field records were submitted to descriptive statistics. A total of 114 different associations were recognized; 30 ants species of the Formicinae, Myrmicinae, Dolichoderinae, and Ponerinae subfamilies associated with 12 homopterans of the Coccidae, Pseudococcidae, Aphididae, Ortheziidae, Aethalionidae, and Membracidae families were found. The sucking insects more common on the coffee plants were: Coccus viridis, Saissetia coffea, Planococcus citri, Toxoptera aurantii and Orthezia sp .. Three types of relationships were identified: mutualism (95,11%), commensalism (4,57%) and depredation (0,32%). The highest number of ants and associated sucking species were registered at the Supia (Caldas) and Líbano (Tolima). The ants indirectly protect the homopteran colonies against natural enemy attacks through cleaning and covers, however, they do not exercise a direct action against fungi, parasites and predators that actas natural control agents and regulate the homopteran population.